Irritable Bowel Syndrome - Anandita, Nur Safira (Majority, 2015)
Abstract Background. In the last two decades, Irritable bowel syndrome has gained considerable attention in the health sector due to the high prevalence and symptoms vary. IBS belongs to a group of chronic gastrointestinal disease known as functional bowel disorders (FBD) are classified by the Rome foundation. Literature review. Clinical symptoms of IBS such as abdominal pain or discomfort in the abdomen and a change in bowel pattern such as diarrhea, constipation or diarrhea and constipation alternately and bloating. Diagnosed on the basis of typical symptoms in the absence of alarm symptoms such as weight loss, rectal bleeding, fever or anemia. Physical examination and diagnostic tests that are currently available are not specific enough to make a diagnosis of IBS, so the diagnosis of IBS is made on the basis of typical symptoms. Methods. I analyzed the results from a variety of articles, researchh and text books. Conclusion. IBS is a functional bowel disease syndrome. No investigation can definitively diagnose IBS. So IBS diagnosis is established when the other is not upright. IBS Treatment includes lifestyle changes, diet, and symptomatic therapy. Keywords: Diet, irritable bowel syndrome, lifestyle, symptomatic therapy. Abstrak Latar Belakang. Pada dua dekade terakhir, Irritable bowel syndrome telah mendapatkan perhatian yang cukup besar di bidang kesehatan akibat semakin tingginya prevalensi dan gejala yang muncul bervariasi. IBS termasuk dalam kelompok penyakit gastrointestinal kronik yang disebut sebagai functional bowel disorders (FBD) yang diklasifikasikan oleh the Rome foundation. Tinjau Pustaka. Gejala klinik IBS berupa nyeri perut atau rasa tidak nyaman di abdomen dan perubahan pola buang air besar seperti diare, konstipasi atau diare dan konstipasi bergantian serta rasa kembung. Didiagnosis atas dasar gejala-gejala yang khas tanpa adanya gejala alarm seperti penurunan berat badan, perdarahan per rektal, demam atau anemia. Pemeriksaan fisik dan tes diagnostik yang sekarang tersedia tidak cukup spesifik untuk menegakkan diagnosis IBS, sehingga diagnosis IBS ditegakkan atas dasar gejala-gejala yang khas tersebut. Metode. Saya menganalisis hasil dari berbagai sumber artikel, hasil penelitian serta teks book. Simpulan. IBS adalah penyakit functional bowel syndrom. Tidak ada pemeriksaan penunjang yang dapat menegakkan diagnosa IBS secara pasti. Maka IBS ditegakkan ketika diagnosis lain tidak tegak. Penatalaksanaan IBS meliputi perubahan gaya hidup, pola makan, dan terapi simptomatik. Kata Kunci : Irritable Bowel Syndrome, gaya hidup, pola makan, terapi simptomatik.